#TITLE_ALTERNATIVE# - DINAN HANIFA (NIM : 12911034), ARUNI
Coastal acoustic tomography experiment was carried out in Bali Strait to measure temperature and ocean currents. It held on March 18th-20th, 2014. Coastal acoustic tomography is a measurement method using sound waves propagation that transmitted and received by the transducer with the principle of reciprocal sound transmission. This research aims to reconstruct temperature and ocean currents by inversion matrix method (inverse problem). Temperature reconstruction is done by using the sound speed propagation equation Mackenzie (1981). Validation for the result was compared with temperature data from the CTD (Conductivity, Temperature, and Depth) measurement and tide data in Pengambengan Station, Bali. Only B2-B3 station data (B2 located in the port of Gilimanuk, Bali and B3 are located in Ketapang, Banyuwangi) is used, with the receiver at B3 that have high SNR (Signal to Noise Ratio) up to 4 dB. Validation of the temperature that correlated with the data CTD reached 99.47%. Reconstruction results of temperature had range 25.9-27.85oC and mean temperature from surface until 20 m below was 26.13-27.85oC. The reconstruction for mean currents had maximum speed of 2.6 m/sec.